2020
DOI: 10.1038/s41598-020-58477-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional lateralization of arithmetic processing in the intraparietal sulcus is associated with handedness

Abstract: Functional lateralization is established for various cognitive functions, but was hardly ever investigated for arithmetic processing. Most neurocognitive models assume a central role of the bilateral intraparietal sulcus (IPS) in arithmetic processing and there is some evidence for more pronounced left-hemispheric activation for symbolic arithmetic. However, evidence was mainly obtained by studies in right-handers. Therefore, we conducted a functional near-infrared spectroscopy (fNIRS) study, in which IPS acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 93 publications
(93 reference statements)
2
9
1
Order By: Relevance
“…While the right intraparietal sulcus is engaged in non-symbolic number magnitude processing, particularly at early ages (Edwards et al 2016;Hyde et al 2010), the left intraparietal sulcus is deeply involved in symbolic number magnitude processing of the numbers at school ages (Vogel et al 2015) in association with language-related areas on the left hemisphere. Supporting our current finding, the right parietal cortex is expected to be involved in the calculation to a greater degree in younger children than the left parietal cortex, according to a recent theoretical model of functional lateralization in the parietal cortex in arithmetic (Artemenko et al 2020).…”
Section: Neurobehavioral Changes During Complex Calculation In Childr...supporting
confidence: 87%
“…While the right intraparietal sulcus is engaged in non-symbolic number magnitude processing, particularly at early ages (Edwards et al 2016;Hyde et al 2010), the left intraparietal sulcus is deeply involved in symbolic number magnitude processing of the numbers at school ages (Vogel et al 2015) in association with language-related areas on the left hemisphere. Supporting our current finding, the right parietal cortex is expected to be involved in the calculation to a greater degree in younger children than the left parietal cortex, according to a recent theoretical model of functional lateralization in the parietal cortex in arithmetic (Artemenko et al 2020).…”
Section: Neurobehavioral Changes During Complex Calculation In Childr...supporting
confidence: 87%
“…The other major finding-reduced WM coherence and shorter length of the left anterior thalamic radiation-might be attributed to insufficiencies in encoding, retrieving and working with arithmetical facts in children with DD. Left lateralized differences in these pathways might be related to hemispheric dominance, which was proposed to be pronounced in arithmetic processing during development (Artemenko et al, 2020). In this neurodevelopmental study, we revealed first evidence that lower math performance corresponded with lower WM coherence and shorter pathways.…”
Section: Discussionmentioning
confidence: 54%
“…Handedness has also been linked to performance in several tasks: in auditory coordination tasks, participants respond faster to stimuli presented on the side contralateral to their preferred hand (Ocklenburg et al 2010). Similarly, in arithmetic processing tasks, left-handers show stronger functional right-sided activity than right-handers (Artemenko et al 2020). Furthermore, approach motivation was found to be associated with left-hemispheric activity in right-handers and right-hemispheric activity in left-handers (Brookshire and Casasanto 2012).…”
Section: Introductionmentioning
confidence: 99%